A review on the oxidative stress in recurrent aphtous stomatitis - Mehryari Mahsa; Mortazavi Nazanin; Sayyadi Fatemeh; Mohsenitavakoli Saman; Zahedpasha Shaghayegh; Mortazaviamiri Seyedhadi; Bijani Ali; Kazemi Hamed Hossein; Motallebnejad Mina (Tehran University of Medical Sciences, 2015)
Background and Aims: The purpose of the present study was to review the studies regarding serological and salivary oxidant / antioxidant status in patients with recurrent aphthous stomatitis (RAS).   Materials and Methods: The literature was searched using key words RAS, Antioxidants, Saliva, Hematinic (s) and Hematinic Acid in the last 10 years, particularly the recent 3 years (2010-2013). At total of 37 clinical trials, 18 case-control articles were selected and evaluated; fulfilling the requirements as the RAS patients having at least 3 oral aphthous attack per year. The exclusion criteria included systemic as well as periodontal diseases, iron deficiency associated anemia, medication usage and smoking.   Conclusion: Almost all lipid-peroxidation studies in serum and saliva were manifested by an increase of malondialdehyde (MDA) concentration in RAS patients compared with controls. This would indicate the role of reactive oxygen species (ROS) in the etiology of the disease. Serum trace elements (Zn, Se) were reduced and Cu was increased in RAS patients in comparison with control individuals. A decreased serum superoxide dismutase (SOD) and an increased salivary SOD were observed in all RAS patients. Catalase (CAT) and uric acid (UA) analyses were non-inclusive. Levels of paraoxonase and arylesterase as well as antioxidant vitamins (A, E, C) were lower in RAS patients than that of controls.